Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 68390 by TawaTawa last updated on 10/Sep/19

Answered by som(math1967) last updated on 10/Sep/19

tan(2tan^(−1) (√((2cos^2 (θ/2))/(2sin^2 (θ/2)))) )+tanθ  =tan{2tan^(−1) (cot (θ/2))}+tan θ  =tan{2tan^(−1) tan((π/2)−(θ/2))}+tan θ  =tan(π−θ)+tanθ  =−tanθ+tanθ=0

tan(2tan12cos2θ22sin2θ2)+tanθ=tan{2tan1(cotθ2)}+tanθ=tan{2tan1tan(π2θ2)}+tanθ=tan(πθ)+tanθ=tanθ+tanθ=0

Commented by TawaTawa last updated on 10/Sep/19

God bless you sir

Godblessyousir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com